How to be a brilliant teaching assistant - Bentham, Susan, 1958- (Routledge Taylor & Francis Group, 2019)
"How to be a Brilliant Teaching Assistant draws on top knowledge from very experienced Teaching Assistants and Sue Bentham's own extensive research to explore the common denominators that unite all brilliant Teaching Assistants. The book explores becoming a brilliant Teaching Assistant as a journey and not an end point, and provides support in the form of examples, discussion points and activities which will help you along the way, whether you're just starting out in your career or you've been an experienced Teaching Assistant for years. This accessible book covers all aspects of the Teaching Assistant role, such as: A brief history of Teaching Assistants Key roles and responsibilities Metacognition and understanding children's learning Delivering high quality lessons alongside teachers Developing useful subject knowledge Undertaking research and professional development Illustrated with activities and discussion points and anecdotes, this book is a source of support, guidance and inspiration for every Teaching Assistant engaged in the ongoing process of becoming an outstanding professional"--